Pelaksanaan Program Pembiasaan Adab Islami Peserta Didik di Sekolah Dasar Alam Terpadu (SDAT) Nurul Haq - Anita Dwi Cahyanti; A. Arif Rofiki; Luluk Wahyu Nengsih; Zulihi; Didik Efendi (Advances In Education Journal, 2026)
Nature school is one of the new concepts of education. Students are taught how to use and keep the nature for life. As one example, schools that applies the concept of a nature school is School of Universe which integrates four curricular that comprises tahfidz, character, leadership, and entrepeunership curriculum. This research aims at analysing and describing the uniqueness or special characteristics of the processes and steps of nature school management in School of Universe, which is located in Muaratami, in developing tahfidz, character, leadership, and entrepeunership curriculum in Elementary School level. Management of Nature School being studied covered the stages of planning, organizing, directing and implementation, and controlling. This research applied qualitative methods and focused on researcher as its instrument. The The data were collected from interview, observation, and documentation studies. Based on the existing data and information This thesis finds and concludes that good and structured process of planning, organizing, directing, and controlling becomes main supporting factor in developing tahfidz, character, leadership, and entrepeunership in elementary school level in the School of Universe. In order to achieve the goals as listed on the tahfidz, character, leadership, and entrepeunership curriculum, it needs detail and consistent planning, organization based on needs, direction and implementation that is in accordance with components of program which has been arranged and planned in advance, as well as regular intensive control using objective instruments that meet students’ learning development.